2017
DOI: 10.5336/dentalsci.2017-55753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anxiety and Depression Levels of Dental Faculty Preclinical Student?s in Term of Various Variables

Abstract: 416), BDI (p=0,083) skorları cinsiyete göre istatistiksel olarak anlamlı farklılık göstermemiştir. Ögrencilerin okudukları sınıfa göre STAI-I (p=0,002) skorunda ve üniversiteye göre BDI (p=0,004) skorunda istatistiksel olarak anlamlı farklı-lıklar saptanmıştır. İlk ve ortaokul eğitim seviyesinde olan babaların çocuklarında BDI skoru daha yüksek bulunmuştur (p=0.015). Fakat, anne eğitim seviyesi ile STAI-I, STAI-II ve BDI skorları istatistiksel açıdan değerlendirildiğinde anlamlı bir ilişki bulunamamıştır. Ayrı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Yıldırım et al compared the anxiety levels of 1stand 2nd-grade students and found that 1st-grade students had higher STAI-S scores. They also found a positive correlation between these students' STAI-S, STAI-T, and Beck Depression Inventory scores, which is consistent with our findings (13).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Yıldırım et al compared the anxiety levels of 1stand 2nd-grade students and found that 1st-grade students had higher STAI-S scores. They also found a positive correlation between these students' STAI-S, STAI-T, and Beck Depression Inventory scores, which is consistent with our findings (13).…”
Section: Discussionsupporting
confidence: 91%
“…Studies on dental anxiety among dental students in the literature have reported higher anxiety levels in first-year students compared to final-year students (7,13,(21)(22)(23). It has been reported that the unfamiliarity with the environment and the city is minimized in thirdyear students but inexplicably increases again in fourthand fifth-year students, and dissatisfaction with social life increases with class level (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation